Penyuluhan dalam Meningkatkan Kesadaran Hukum di Desa Mangli, Randudongkal, Pemalang - Mutiara, Lediana Tia; Anwar, Umar; Equatora, Muhammad Ali (CV. Literasi Indonesia, 2023)
Counseling in the context of community service related to the legal awareness education program in increasing understanding and knowledge for the Pekalongan Class II Bapas correctional clients and the Mangli Village community is essential, which is aimed explicitly at correctional clients so they do not repeat criminal acts (recidivist). For the people of Mangli Village, counseling functions to prevent violations of criminal acts, especially in Mangli Village. The method used is the lecture method, namely presentation, explaining, and opening a question and answer session and conveying opinions from clients or the public. The results of the implementation of PKM activities are in the form of counseling related to legal awareness, namely community development before and after being given counseling to become more aware of the importance of the level of public attention in legal awareness. The village community gained more knowledge than before being given counseling regarding understanding legal cognition.